Effects of Base Materials (α-Alumina and/or γ-Alumina) on Volatile Organic Compounds (VOCs)-Sensing Properties of Adsorption/Combustion-Type Microsensors - Takeo Hyodo; Yuma Matsuura; Genki Inao; Takahiko Sasahara; Yasuhiro Shimizu; Taro Ueda (Chemosensors)
The sensing properties of adsorption/combustion-type microsensors using 5 wt% Pt-loaded aluminas, which consist of two kinds of alumina (α-Al2O3 and γ-Al2O3), as sensing (catalytic) materials for ethanol and toluene, were investigated in air, and the mixing effects of α-Al2O3 with γ-Al2O3 on the dynamic and static responses of the sensors were discussed in this study. The mixing of 50 wt% α-Al2O3 with γ-Al2O3 was the most effective in enhancing the dynamic responses to ethanol, which originated from the flash combustion behavior of ethanol and/or their partially decomposed products adsorbed on the sensing films from 150 °C to 450 °C, while further mixing of α-Al2O3 with γ-Al2O3 tended to increase the dynamic responses to toluene. On the other hand, the static responses to both ethanol and toluene, which arise from their catalytic combustion at elevated temperatures (450 °C), mainly increased with an increase in the addition of α-Al2O3 in the 5 wt% Pt-loaded aluminas. These results indicate that the synergistic effects of the catalytic activity and the thermal conductivity of the 5 wt% Pt-loaded aluminas are the most important for the sensing properties of these sensors to ethanol and toluene.